ATRIBUT PROYEK DAN MUDHARIB DALAM PEMBIAYAAN MUDHARABAH PADA BANK SYARI’AH DI INDONESIA - Muhammad Muhammad (Journal of Indonesian Economy and Business (JIEB), 2006)
The research is concerned with the project and mudharibs’ attributes in the mudharabah financing in the Sharia Banks, Indonesia. The Study has been focused to search (1) the projects attributes might be considered by the banks in dealing with mudharabah financing; and (2) the mudharib’s attributes which will be financed by the banks. The study is basically explorative in nature. The study was conducted to 84 out of 89 Islamic or Sharia Rural Bank in Indonesia. 64 of respondents (76.19 percent) have returned the questionnaires. Certain numbers of banks’ managers were also interviewed deeply. The returned questionnaires were adequate to be examined statistically. The quantitative method is then applied to examine the factors considered statistically. The study has found that there are six attributes considered from the mudharabah projects point of view, which include the prospect of project, availability of collateral, healthiness of project, project’s financial statement, clarity of contract conditions, and conformity of time period. In regrad to mudharib attributes, the study has also concluded five characteristics which are considered important. They include the business capacity, (personal) collateral, mudharibs’ reputation and family background, and their business commitments.